Tipe-Tipe Kualitas Perkawinan Orang Yogyakarta - Siti Rohmah Nurhayati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to explore the types of marital quality. A survey was distributed to 316 participants with the characteristics of having been married for at least five years and identified themselves as people of Yogyakarta, which were obtained purposively. The instrument used marital quality scale which was analyzed quantitatively using cluster analysis. Grouping using cluster analysis was based on indicators of marital quality, namely connectivity, passion, complementarity, mutual respect, mutual acceptance, sharing roles, carrying out the roles with responsibility, harmony, and happiness. The results of the analysis showed that there were three types of marital quality that is happy, functional, and survival type. The happy type is the best quality type that scores above the average population score for all indicators. The second, functional type, has a score below the first type, with variations for each indicator. The third type is the type with the lowest score compared to the other two types.